Association between diet quality scores and risk of overweight and obesity in children and adolescents - Xiaoyun Zheng; Hong Wang; Huiwen Wu (BMC, 2023)
Abstract Background This study examined the associations of diet quality assessed by Healthy Eating Index 2015 (HEI-2015), Alternative Healthy Eating Index 2010 (AHEI-2010), Mediterranean Diet (MedDiet) and overweight/obesity in children and adolescents. Methods This cross-sectional study used data of participants aged 2-19 years from National Health and Nutrition Examination Survey (NHANES) 2005-2018. The weighted logistic regression model was adopted to explore the association between diet quality scores and overweight, obesity in children and adolescents. Subgroup analysis was also performed based on sex. Results A total of 9,724 participants were included in children group (2-11 years old), and 5,934 were adolescent group (12-19 years old). All participants were divided into based on the BMI-for-age: underweight and normal, overweight and obesity groups. After adjusting for age, race, poverty-income ratio, maternal smoking during pregnancy and total energy, HEI-2015 and MedDiet scores were related to the risk of overweight in children, and only MedDiet scores remained associated with a decreased risk of obesity in children. MedDiet scores were associated with a decreased risk of overweight, obesity in adolescents, respectively, after adjusting age, sex, race, poverty-income ratio, cotinine, total energy and physical activity. The similar results in male participants were also found. Conclusion Higher MedDiet scores were associated with lower the risk of overweight and obesity, respectively, particularly for male children and adolescents. The higher HEI-2015 scores were also related to the risk of overweight in children.